Abandonment of traditional saltworks facilitates degradation of halophytic plant communities and Carpobrotus edulis invasion. Issue 3 (29th April 2019) - Chefaoui, Rosa M.; Chozas, Sergio
Abstract: Aims: In Mediterranean countries, traditional salt exploitation has been practiced over centuries. However, there is a progressive reduction of active saltworks, causing changes in the adjacent halophytic communities and, ultimately, the invasion by opportunistic plant species. Assessing the impact of land use change is key to understanding and protecting these fragile wetland ecosystems. Here, we explore how the abandonment of saltworks is impacting plant communities. We assess if the reduction in saltworks activity alters the composition of protected halophytic communities and favours the invasion by Carpobrotus edulis, an invasive species in many coastal regions throughout the world. Location: The Natural Park of Ria Formosa (Algarve, Portugal). Methods: We studied variations in the structure of halophytic communities affected to different degrees by C. edulis over three saltworks land use regimes in the Ria Formosa. Plant cover and soil salinity were estimated in a total of 60 transects pertaining to two saltworks complexes harbouring different land use and hydrologic regimes. We performed a non‐metric multidimensional scaling ordination of saltworks based on plant cover and identified the indicator species of each saltworks class. Results: We found that plant communities significantly varied among types of saltworks according to the pattern of soil salinity and hydrologic regime. We identified C. edulis as the main indicator species of the abandoned saltworks' communities, characterized by less saline soils and being desiccated in summer. Conclusions: Land‐use change caused by the abandonment of salinas facilitated the transition of halophytic into psammophytic communities and the invasiveness of C. edulis . The maintenance of traditional saltworks activities is vital for the preservation of this fragile wetland ecosystem. Abstract : We combined field data with the use of geographical information systems and statistical analyses to assess if the abandonment of saltworks alters the composition of protected halophytic communities and favours the invasion by C. edulis . We found that land use change caused by the abandonment of salinas facilitated the transition of halophytic into psammophytic communities and the invasiveness by C. edulis .